2006
DOI: 10.1111/j.1365-2117.2006.00304.x
|View full text |Cite
|
Sign up to set email alerts
|

A Neoproterozoic glacially influenced basin margin succession and ‘atypical’ cap carbonate associated with bedrock palaeovalleys, Mirbat area, southern Oman

Abstract: The Ayn Formation of the Neoproterozoic Mirbat Group comprises <400 m of little‐deformed, glacially influenced basin margin deposits. These deposits are preserved in several palaeovalleys eroded in crystalline basement and overlain by a discontinuous cap carbonate. The Ayn Formation and the cap carbonate, which are superbly exposed along a 20 km SW–NE‐striking escarpment in south Oman, provide important insights into the processes operating on a basin margin during a Neoproterozoic glaciation and its demise. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
14
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(15 citation statements)
references
References 98 publications
(209 reference statements)
1
14
0
Order By: Relevance
“…GLOBAL NEOPROTEROZOIC GLACIAL PALAEOLATITUDES Despite a new, precise U-Pb TIMS age of 711.5+ 1.1 Ma for the Ghubrah diamictite in the Jebel Akhdar region of northeastern Oman ; all sources of error included), its palaeolatitude remains poorly constrained. However, unmetamorphosed deposits of the possibly Ghubrah-correlative, lower Mirbat sandstone/diamictite assemblage, now renamed as the Ayn Formation (Rieu et al 2006(Rieu et al , 2007, yield a low-reliability palaeomagnetic direction (Kempf et al 2000). This under-defined magnetization (n ¼ 10 samples from two sites) would imply a palaeolatitude of 09 + 48 for the Ayn Formation, but we cannot include it in our final compilation due to the severely limited sample size.…”
Section: India To Nubiamentioning
confidence: 92%
“…GLOBAL NEOPROTEROZOIC GLACIAL PALAEOLATITUDES Despite a new, precise U-Pb TIMS age of 711.5+ 1.1 Ma for the Ghubrah diamictite in the Jebel Akhdar region of northeastern Oman ; all sources of error included), its palaeolatitude remains poorly constrained. However, unmetamorphosed deposits of the possibly Ghubrah-correlative, lower Mirbat sandstone/diamictite assemblage, now renamed as the Ayn Formation (Rieu et al 2006(Rieu et al , 2007, yield a low-reliability palaeomagnetic direction (Kempf et al 2000). This under-defined magnetization (n ¼ 10 samples from two sites) would imply a palaeolatitude of 09 + 48 for the Ayn Formation, but we cannot include it in our final compilation due to the severely limited sample size.…”
Section: India To Nubiamentioning
confidence: 92%
“…These features are present in outcrop at several sites in Africa, the Middle East, South America and Australia (e.g. Beuf et al 1971;Visser 1988;Vaslet 1990;Eyles & de Broekert 2001;Le Heron et al 2004;Eschard et al 2005;Rieu et al 2006;Gutiérrez-Marco et al 2010;Hoffman & Macdonald 2010;Keller et al 2011;Fig. 2) and have been identified in the deep subsurface during hydrocarbon investigations (McGillivray & Husseini 1992;Smart 2000;Hirst et al 2002;McDougall et al 2006;Melvin & Sprague 2006).…”
Section: Pre-pleistocene Tunnel Valleysmentioning
confidence: 94%
“…Recent age dates and sedimentological studies suggested that the Sturtian glaciation may have lasted long from c. 750 to c. 663 Ma and its initiation and termination are globally diachronous, with potentially multiple episodes or a series of short-lived glaciations (e.g. Lund et al, 2003;Eyles and Januszczak, 2004;Fanning and Link, 2004;Zhou et al, 2004;Kendall et al, 2006;Rieu et al, 2006;Zheng et al, 2007). In contrast, the Gaskiers glaciation may have been regional and lasted less than 1 million years (Myr) around 582 Ma (Bowring et al, 2003;Halverson et al, 2005;Halverson, 2006).…”
Section: Introductionmentioning
confidence: 99%